Economic evaluation of projects in the electricity supply industry. - Khatib, Hisham, 1936- (London : Institution of Engineering and Technology, 2003)
In a highly capital-intensive environment such as the electricity supply industry, it is essential that those working in the electrical power field - on either the engineering or management side - understand the methodologies of evaluating projects in order to fully comprehend and analyse investment proposals and decisions. This new book, a substantially revised and updated edition of the author's previous work "Financial and Economic Evaluation of Projects in the Electricity Supply Industry" (IEE/1996), takes a broad introductory approach and includes extensive consideration of market and environmental issues. It introduces the reader to the tools and techniques of financial analysis and evaluation, as well as clean environmental technologies and costs. New topics introduced include electricity trading and risk management, evolving electricity utilities, and new and future generation technologies in a carbon-constrained world